Desain dan Perancangan Alat Welding Holder untuk Pengelasan Pelat pada Las GMAW - Kurniawan, Ipung; Sodikin, Jenal; Pujono; Setia Pribadi, Joko; Santoso, Agus (Politeknik Negeri Cilacap, 2023)
One of the metal welding processes required by the manufacturing industry is gas arc welding (GMAW). The welding process that is capable of transmitting large amounts of heat at high speeds is gas electric welding or GMAW (Gas Metal Arc Welding). The design mechanism for the movement of the X and Y axes in the development of GMAW welding holders uses the stages of finding ideas, studying literature, identifying problems, designing, making tools and testing machines. The purpose of this study was to design a mechanism for moving the X and Y axes in the development of an automatic GMAW torch holder machine and to calculate the machine elements in the development of an automatic GMAW torch holder machine. The process of designing and constructing the movement of the X and Y axes in the development of an automatic GMAW welding torch holder machine is carried out with a design procedure that is used as a reference in solving problems. The track shaft uses chrome steel with a diameter of 25 mm and a length of 800 mm, Linear bearings use type SCS25UU with an inner diameter of 25 mm, Linear rail shafts use aluminum alloy material with a diameter of 25 mm which is used to support the end of the track shaft, Ballscrew uses the SFU 2005 type with a size of 3/4 inch which is equipped with a ballscrew nut and also a nut housing, Bearing block uses a UCP type with a diameter of 20 mm, Flexible coupling measuring 5 mm to 10 mm is used to connect the drive screw with the stepper motor, The stepper motor is used as the main power to drive the drive screw type Nema 17 (17HD48002H-22B) with the specifications Step Angle: 1.8o, Rated Current: 1.5 Ampere, Voltage : 2.7V.